A Four-Sided Anti-Doll: Eleanor Marx and 21st Century Socialist Feminism (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
In this text, we commen on the work of the historian Rachel Holmes about the life of Eleanor Marx, recently translated into Portuguese. In reading the biography, her socialist activism as well as her career in theater, in which she worked from 1875 until the end of her life, stands out. In this sense, her role as a translator of proto-feminist works, such as Madame Bovary, by Flaubert and Casa de Muñecas, by Henrik Ibsen, from whom she translated other dramaturgical texts, is highlighted. Notable in the comment is the work carried out by the youngest daughter of Karl Marx, together with the Social Democratic Federation, the Socialist League and the Union of Gas workers, organizations in which she acted in the field of education, agitation and propaganda and translation, as well as in internationalist solidarity. In addition, her recognized militancy along with socialist feminism of the late nineteenth century stands out, a subjecton which she wrote The question of women - from a socialist point of view, in 1886.
Keywords: Eleanor Marx; Feminism; Dramatic arts; Socialism